The identification and structural analysis of potential 14‐3‐3 interaction sites on the bone regulator protein Schnurri‐3 - Soini, Lorenzo; Leysen, Seppe; Crabbe, Tom; Davis, Jeremy; Ottmann, Christian (Acta crystallographica. Section F, Structural biology communications, 2021)
14‐3‐3 proteins regulate many intracellular processes and their ability to bind in subtly different fashions to their numerous partner proteins provides attractive drug‐targeting points for a range of diseases. Schnurri‐3 is a suppressor of mouse bone formation and a candidate target for novel osteoporosis therapeutics, and thus it is of interest to determine whether it interacts with 14‐3‐3. In this work, potential 14‐3‐3 interaction sites on mammalian Schnurri‐3 were identified by an in silico analysis of its protein sequence. Using fluorescence polarization, isothermal titration calorimetry and X‐ray crystallography, it is shown that synthetic peptides containing either phosphorylated Thr869 or Ser542 can indeed interact with 14‐3‐3, with the latter capable of forming an interprotein disulfide bond with 14‐3‐3σ: a hitherto unreported phenomenon. The structures of two peptide motifs of Schnurri‐3 in complex with 14‐3‐3 are reported.